2019
DOI: 10.1021/acs.jmedchem.8b01288
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Type-IV Inhibitors of BRAF Kinase That Block Dimerization and Overcome Paradoxical MEK/ERK Activation

Abstract: Despite the clinical success of BRAF inhibitors like vemurafenib in treating metastatic melanoma, resistance has emerged through "paradoxical MEK/ERK signaling" where transactivation of one protomer occurs as a result of drug inhibition of the other partner in the activated dimer. The importance of the dimerization interface in the signaling potential of wildtype BRAF in cells expressing oncogenic Ras has recently been demonstrated and proposed as a site of therapeutic intervention in targeting cancers resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Beneker et al truncated this peptide at each end and identified 504‐518 as a tighter binder than the original sequence (0.13 vs 3.8 μM for 503‐521) 40 . The shortened peptide 504‐518 fused to a Tat CPP showed a reduction in paradoxical MEK activation in cells treated with Vemurafenib, another ATP‐competitive BRaf inhibitor.…”
Section: Ras Familymentioning
confidence: 99%
“…Beneker et al truncated this peptide at each end and identified 504‐518 as a tighter binder than the original sequence (0.13 vs 3.8 μM for 503‐521) 40 . The shortened peptide 504‐518 fused to a Tat CPP showed a reduction in paradoxical MEK activation in cells treated with Vemurafenib, another ATP‐competitive BRaf inhibitor.…”
Section: Ras Familymentioning
confidence: 99%
“…The first-generation Raf inhibitors, including Vemurafenib (VEM) [51] , [52] and Dabrafenib [53] , are ATP competitive inhibitors that show promising early efficacy, but drug resistance quickly develops [46] , [47] , [54] , [55] , [56] . New inhibitors have been developed including pan-Raf inhibitors (such as LY3009120) [57] that bind to both protomers in Raf dimers, paradox breakers that selectively bind to B-Raf dimers, and allosteric inhibitors that target other sites apart from the ATP binding pocket [58] , [59] . Despite this progress, long term survival rates remain low and additional treatment options are necessary [60] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, given the unique activating and catalytic mechanisms of RAF family kinases, targeting RAF/RAF and RAF/MEK interactions has become an attractive strategy for designing novel RAF inhibitors [76] . Although no small molecular inhibitors that target RAF/RAF dimer interface have been developed at present, several groups have demonstrated that disrupting RAF/RAF dimers by using peptide inhibitors can effectively block hyperactive ERK signaling and thereby inhibit the growth of cancer cells harboring active RAF or RAS mutations [177][178][179] , indicating that the RAF/RAF dimer interface is indeed a valid target for drug development. As for RAF/MEK interaction, it is dynamically altered in the process of MEK phosphorylation by RAF, as described above.…”
Section: Developing Next-generation Raf Inhibitors For Overcoming Drug Resistancementioning
confidence: 99%